1992
DOI: 10.1104/pp.99.4.1540
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Uptake and Metabolism in the Developing Endosperm of Tassel-seed Tunicate (Ts-5 Tu) Maize

Abstract: Factors regulating assimilate transport into developing maize (Zea mays L.) kernels have been difficult to determine because of the structural complexity of basal kernel tissues and the damage that results from tissue dissection. The sensitivity of maize kernels to experimental manipulation is such that substantial maternal tissue is required to support kernel growth in vitro. Consequently, sugar transport experiments with isolated seed tissues or detached kernels have not unequivocally demonstrated how sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Similar kinetics were observed for PCMBS-sensitive sucrose uptake from the endosperm cavity of developing wheat grain by the modified 61 aleurone/sub-aleurone transfer cell complexes abutting the endosperm cavity (Wang et al 1995b). In contrast, Griffith et al (1987) found that sugar accumulation by dermal transfer cells enveloping the endosperm of developing Zea mays seed was linearly dependent upon the external sugar concentration (but see Thomas et al 1992). However, excepting the Vicia cotyledon (McDonald et al 1995 and this paper), the contribution of the transfer cells to the observed transport kinetics remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Similar kinetics were observed for PCMBS-sensitive sucrose uptake from the endosperm cavity of developing wheat grain by the modified 61 aleurone/sub-aleurone transfer cell complexes abutting the endosperm cavity (Wang et al 1995b). In contrast, Griffith et al (1987) found that sugar accumulation by dermal transfer cells enveloping the endosperm of developing Zea mays seed was linearly dependent upon the external sugar concentration (but see Thomas et al 1992). However, excepting the Vicia cotyledon (McDonald et al 1995 and this paper), the contribution of the transfer cells to the observed transport kinetics remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, the kinetics of sugar uptake by the endosperm of developing embryos of Zea mays exhibited kinetics consistent with simple diffusion (Griffith et al 1987). However, this transport behaviour could be artifactual resulting from mechanical damage incurred during tissue preparation (Thomas et al 1992). Indeed, uptake of sucrose from the endosperm cavity across the plasma membranes of the modified aleurone-sub aleurone transfer cell complex appears to occur by a carriermediated and energy-dependent transport mechanism (Wang et al 1995b).…”
Section: Introductionmentioning
confidence: 90%
“…Kernel development is supported by sucrose transferred from phloem, across pedicel and basal transfer cells (Aoki et al. , 1999; Thomas et al. , 1992) to the main endosperm compartments and embryo (Shannon, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of sugar influx by exposed endosperm of developing maize kernels suggested that sugar influx occurred by passive diffusion alone (Griffith et al 1987). However, this behaviour could result from mechanical damage to the uptake mechanism (Felker et al 1990; Thomas et al 1992). The developing wheat grain appears to be a more robust experimental model.…”
Section: Filial Transport Mechanismsmentioning
confidence: 99%